R-Baclofen Treatment Corrects Autistic-like Behavioral Deficits in the RjIbm(m):FH Fawn-Hooded Rat Strain - Anita Varga; Rita Kedves; Katalin Sághy; Dénes Garab; Ferenc Zádor; Balázs Lendvai; György Lévay; Viktor Román (MDPI AG, 2024)
The Fawn-hooded rat has long been used as a model for various peripheral and central disorders and the data available indicate that the social behavior of this strain may be compromised. However, a thorough description of the Fawn-hooded rat is unavailable in this regard. The objective of the present study was to investigate various aspects of the Fawn-hooded rat's social behavior in depth. Our results show that several facets of socio-communicational behavior are impaired in the RjIbm(m):FH strain, including defective ultrasonic vocalizations in pups upon maternal deprivation, reduced social play in adolescence and impaired social novelty discrimination in adulthood. In addition, Fawn-hooded rats exhibited heightened tactile sensitivity and hyperactivity. The defects observed were comparable to those induced by prenatal valproate exposure, a widely utilized model of autism spectrum disorder. Further on, the pro-social drug R-baclofen (0.25-1 mg/kg) reversed the autistic-like defects observed in Fawn-hooded rats, specifically the deficiency in ultrasonic vocalization, tactile sensitivity and social novelty discrimination endpoints. In conclusion, the asocial, hypersensitive and hyperactive phenotype as well as the responsivity to R-baclofen indicate this variant of the Fawn-hooded rat strain may serve as a model of autism spectrum disorder and could be useful in the identification of novel drug candidates.